Pengaruh penambahan tepung ampas kelapa terhadap daya terima dan komposisi gizi pada nugget udang - Dewirna, Cintia Balqis; Hadi, Abdul (Poltekkes Kemenkes Aceh, 2025)
Background: Nuggets are made from animal-based ingredients such as meat, chicken, fish and others. Nuggets are usually served in a rectangular shape. To add nutritional value to this shrimp nugget, it is formulated with coconut pulp flour which has good nutritional content for the body. Coconut pulp flour has a high food fiber content.Objectives: The purpose of this study was to determine the effect of the addition of coconut pulp flour on the acceptability and nutritional content of shrimp nuggets with the addition of 20, 40, and 60 grams of coconut pulp flour to shrimp nuggets whether it affects the acceptance of nuggets in terms of color, taste, aroma, and texture, as well as their chemical quality in terms of water content, ash, carbohydrates, fat, and protein.Methods: This research is experimental in nature with the experimental design used being a Completely Randomized Design (CRD) Non Factorial, namely by carrying out three treatments and three repetitions (3 x 3 = 9 experimental units). The variables studied in this study were organoleptic tests which included (color, aroma, texture, taste) and Proximate Tests (water content, ash content, Protein, Fat, Fiber and Carbohydrate content) of Shrimp Nuggets.Results: The addition of coconut pulp flour to shrimp nuggets significantly changed their color, scent, and texture, but had no discernible influence on their flavor, according to organoleptic tests. Adding 20 grams of coconut pulp flour is the most beloved part in terms of appearance, smell, flavor, and crumbiness. Adding coconut pulp flour to shrimp nuggets changed their water, ash, fat, and protein content significantly, but their carbohydrate content remained unaffected in the chemical characteristics test.Conclusion: The addition of coconut husk flour to nuggets had a significant effect on the color of the nuggets produced with a P value of 0,001, on the aroma of the nuggets produced with a P value of 0,003, on the texture of the nuggets produced with a P value of 0,002, and had no significant effect on the taste of the nuggets produced with a P value of 0,066. The results of the chemical property test showed that the addition of coconut husk flour had a significant effect on moisture content, ash content, fat, protein, and fiber, and no significant effect on carbohydrates.